Modeling Poliovirus Transmission in Borno and Yobe, Northeast Nigeria. Issue 2 (29th April 2020) - Kalkowska, Dominika A.; Franka, Richard; Higgins, Jeff; Kovacs, Stephanie D.; Forbi, Joseph C.; Wassilak, Steven G. F.; Pallansch, Mark A.; Thompson, Kimberly M.
Abstract: Beginning in 2013, multiple local government areas (LGAs) in Borno and Yobe in northeast Nigeria and other parts of the Lake Chad basin experienced a violent insurgency that resulted in substantial numbers of isolated and displaced people. Northeast Nigeria represents the last known reservoir country of wild poliovirus (WPV) transmission in Africa, with detection of paralytic cases caused by serotype 1 WPV in 2016 in Borno and serotype 3 WPV in late 2012. Parts of Borno and Yobe are also problematic areas for transmission of serotype 2 circulating vaccine‐derived polioviruses, and they continue to face challenges associated with conflict and inadequate health services in security‐compromised areas that limit both immunization and surveillance activities. We model poliovirus transmission of all three serotypes for Borno and Yobe using a deterministic differential equation‐based model that includes four subpopulations to account for limitations in access to immunization services and dynamic restrictions in population mixing. We find that accessibility issues and insufficient immunization allow for prolonged poliovirus transmission and potential undetected paralytic cases, although as of the end of 2019, including responsive program activities in the modeling suggest die out of indigenous serotypes 1 and 3 WPVs prior to 2020. Specifically, recent and current efforts to access isolated populations and provide oral poliovirus vaccine continue to reduce the risks of sustained and undetected transmission, although some uncertainty remains. Continued improvement in immunization and surveillance in the isolated subpopulations should minimize these risks. Stochastic modeling can build on this analysis to characterize the implications for undetected transmission and confidence about no circulation.